In vitro control of Staphylococcus aureus (NCTC 6571) and Escherichia coli (ATCC 25922) by Ricinus communis L. - Christy Jeyaseelan, E.; Justin Jashothan, P.T. (Asian Pacific Tropical Biomedical Magazine, 2012)
Objective: To evaluate antibacterial activity of hot and cold ethanol and methanol leaf extracts of Ricinus communis L (R. communis) against Staphylococcus aureus (S. aureus) (NCTC 6571) and Escherichia coli (E. coli) (ATCC 25922). Methods: Leaf powder of R. communis L. was extracted with hot (in Soxhlet) and cold ethanol and methanol, separately. The antibacterial activity of the extracts was determined by agar well diffusion and macro broth dilution methods. The extracts were also subjected to phytochemical analysis. Results: All the four test extracts showed inhibition on both S. aureus and E. coli. Hot and cold ethanol extracts revealed significantly (P < 0.05) higher inhibition on S. aureus than methanol extracts, and the hot ethanol extract had the lowest minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values (5 mg/mL and 10 mg/mL, respectively). E. coli was highly inhibited by hot extracts of both ethanol and methanol with the MIC and MBC of 40 mg/mL and 80 mg/mL, respectively. Phytochemical analysis revealed the presence of saponins, cardiac glycosides, tannins, flavonoids and terpenoids in all test extracts. Conclusions: This study demonstrates that the hot and cold methanol and ethanol extracts are potential sources for control of S. aureus and E. coli. Especially, the hot and cold extracts of ethanol are more inhibitive against S. aureus even at lower concentration. Further study is needed to identify the specific bioactive compounds, their mode of action and their nontoxic nature in vivo condition.
Keywords: Antibacterial activity; Escherichia coli; Extract; Minimum bactericidal concentration; Minimum inhibitory concentration; Ricinus communis; Staphylococcus aureus